Multiple health risk behaviors, including high consumption of ultra-processed foods and their implications for mental health during the COVID-19 pandemic - Coletro, Hillary Nascimento; Mendonça, Raquel de Deus; Meireles, Adriana Lúcia; Machado-Coelho, George Luiz Lins; Menezes, Mariana Carvalho de (Frontiers in Nutrition, 2022)
Background and aim: The growing increase in illnesses related to diet and behavior has drawn the attention of many epidemiologists who have attributed such changes to the epidemiological and nutritional transition. Thus, the aim of this study is to evaluate the association between the combined occurrence of health risk behavior, such as, sedentary lifestyle, high weekly consumption of ultra-processed foods, and non-daily consumption of fruits and vegetables and anxiety or depression symptoms in adults. Methods: This is a cross-sectional study based in an epidemiological survey in two cities in Brazil. The outcome, anxiety and depression symptoms were assessed using Generalized Anxiety Disorder 7-item and Patient Health Questionnaire-9. Food consumption was assessed using a qualitative food frequency questionnaire referring to consumption within the last 3 months and separated into the consumption of fruits and vegetables and consumption of ultra-processed foods, categorized according to NOVA classification. Sedentary behavior was assessed considering the amount of time sitting or reclining per day reported by the participants and categorized into less than nine hours of sitting or reclining time and nine hours or more. For analysis, adjusted Poisson regression was used to estimate the prevalence ratio and 95% confidence interval. Results: Those with the combined risk behaviors, non-daily consumption of fruits and vegetables and high consumption of ultra-processed foods, had a prevalence ratio 2.6 higher for symptoms of mental disorder (PR: 2.6 and 95%IC: 1.1 – 6.5), as well as those with the co-occurrence of the three risk behaviors had a prevalence ratio 2.8 higher for symptoms of mental disorder (PR: 2.8 and 95%IC: 1.3 – 6.1). Conclusion: The present study revealed that, the existence of a combined occurrence of two and three health risk behaviors led to a higher prevalence of symptoms of anxiety or depression.